A Critical Analysis of Determinants Influencing the Effectiveness of Academic Staff Training and Development in Nigerian Tertiary Institutions - Zahra, Sulaiman Fatima; Dennis, Aidelokhai; Musa, Usman; Nmadu, Timothy; Idris, Abu (NIU Journal of Social Sciences, 2025)
This paper critically examines the key determinants influencing the effectiveness of academic staff training and development in Nigerian tertiary institution. Using qualitative content analysis, the study explores institutional policies, funding mechanisms, faculty motivation, infrastructural capacity, and external influences that shape staff development outcomes. The findings reveal that although significant progress has been made—particularly through interventions by the Tertiary Education Trust Fund (TETFund)—persistent challenges such as inadequate institutional funding, weak policy implementation, politicized access to training opportunities, and low faculty engagement hinder the effectiveness of training programs. The paper concludes by proposing actionable recommendations, including strengthening institutional frameworks, improving resource allocation, enhancing motivation systems, and promoting international collaborations to boost academic staff development in Nigerian tertiary institutions. Keywords: Academic staff development, Training effectiveness, Tertiary education, Nigerian universities, Institutional policy.